Reflexo invertido: a tradução do conto "Memento Mori" para o cinema - Silva, Taynan Leite da (2019)
The link between literature and cinema is a fact that can be proven by the large number of literary works adapted to the seventh art. This relationship is the motivation for the comparative study developed here, which focuses on analyzing the short story “Memento Mori” (2001), by Jonathan Nolan, and its film adaptation, Amnésia (2000), Brazilian translation for the original title Memento, directed by Christopher Nolan. In the short story as well as in the film, the main character suffers from a recent memory loss and seeks revenge for the death of his wife, which would have occurred in the same violent act that caused his inability to form new memories. The film gained special attention from critics for its atypical narrative, immersing the viewer in the character’s forgetfulness. Aiming to identify the elements of approximation and distance between the works, it starts from the analysis of the generative path, instrument used by Semiotics, to identify elements in the different levels of meaning production: discursive, narrative and fundamental, both in the text and in the adaptation, in order to obtain the necessary data to reflect on how the works dialogue with each other, with regard to approximations and distances, and what effects of meaning were produced by the adaptation arrangement. Time, memory, identity, revenge, morality and truth are basic themes in both works and reveal, in the deep structure of the story and the film, the relationship between nature and culture and death and life. After this analysis, we move on to the study of passionality, or state of soul, the analysis of the passions present in the works, story and film, and their implications for the subject's journey. The feeling of loss and anger are emotions that displace the subject and incite him to seek revenge. Passionality works as something that motivates the character to live, even in the face of a limiting disability. It is concluded that the adapted work functions as a starting point and not as an end and that the translation produces new meanings that result mainly from the assembly and insertion of new information, characters, and events. Concerning theoretical support, the present study is based on the semiotic discussions proposed by Greimas and Courtés (2016), Greimas and Fontanille (1993), José Luiz Fiorin (1995; 1996), and Diana Luz Pessoa de Barros (2002); in the cinema theory of André Bazin (2018), Marcel Martin (1990), and Jacques Aumont (1995); and the adaptation theory proposed by Linda Hutcheon (2006) and Robert Stam (2006).